C/C++ mathematical algorithms for scientists and engineers - Shammas, Namir Clement (McGraw-Hill, 1996)
The book covers popular analyisis and statistical topics. It provides C source code all chapters, it offers the C++ version for the cases where using C++ classes offers as a special advantage. This book also focuses on the algorithms involved in implementing the various methods such as BASUC and Pascal